Geographic information systems in action - DeMers, Michael N. (Wiley, 2017)
TRY (FREE for 14 days), OR RENT this title : www.wileystudentchoice.com Geographic Information Systems in Action, 1st Edition offers content that not only teaches GIS techniques, the ideas behind them, and how they work, but also--through a series of graded, hands-on content oriented activities--challenges students to think through what they are doing and why before going on to practical ArcGIS exercises. This deeper understanding, and the superior problem-solving skills students gain from using the text, will also make them highly valuable employees, in addition to well-informed students.